Influence of Laser Energy on the Structural and Optical Properties of Sn Nanoparticles produced with Laser-Induced Plasma - Raghad T. Ahmed; Ala F. Ahmed (Iraqi Journal of Physics)
This study aimed to investigate the structure and optical properties of Sn nanostructures. Thin tin (Sn) films were deposited on glass substrates using the pulsed laser deposition method. Nd:YAG laser with fundamental wavelengths of 532 nm and 1064 nm was used to create Sn nanostructures with varying energies of 400 mJ to 700 mJ and the same frequency of 6 Hz. The tin powder was compressed into a disc with a one-centimetre diameter to serve as a sample. The X-ray diffraction (XRD) pattern showed a crystalline structure with several Sn nanostructures peaks at various energies (400–700 mJ). The results revealed a crystalline size of 65.90 nm and 86.55 nm at 700 mJ, while the size was 40.19 nm and 17.19 at 400 mJ for the given wavelengths (532nm and 1064 nm), respectively. The appearance of Sn nanostructures and the aggregation of, particularly in the form of cauliflower, were revealed in Field emission scanning electron microscopy (FE-SEM) images. The results of the dispersive energy X-ray spectroscopy (EDS) analysis showed that various amounts of tin, carbon, and oxygen were present. Additionally, the optical characteristics were investigated of each film using absorbance spectra, which covered a range of wavelengths from 190 to 1100 nm. As the laser power increased, the band gap energy values in the optical properties decreased, falling into the ranges of 3.06 to 1.65 eV and 3.22 to 1.82 eV at 1064nm and 532nm, respectively.